THE ROLE OF ESTROGEN AND PROGESTERONE ON VAGINAL CYTOLOGY DURING PROLIFERATIVE AND SECRETARY PHASES OF MENSTRUAL CYCLE IN WOMEN WITH POLYCYSTIC OVARIAN SYNDROME (Iraqi Journal of Medical Sciences, 2017)
Background: In the course of cyclic hormonal fluctuation, cytological changes in the vaginal epithelium can be correlated with the phases of the menstrual cycle, this can be utilized in diagnosis of hormonal status in women with pathological cycles as in polycystic ovarian syndrome (PCOS). Objective:To evaluate the effects of estrogen (E2) and progesterone hormones in PCOS on the vaginal cytology in different phases of menstrual cycle, and its relation to ovulation period.Methods: A non-random sample of one hundred women were enrolled in this study, divided into two groups; 50 women free from PCOS, and 50 were PCOS according to the criteria of Rotterdam 2003. All were underwent hormonal assay including estrogen and progesterone on 2nd and 21st day of the cycle respectively, vaginal smears cytology on the 2nd day, 14th and 21st day of the cycle, stained with H&E, the (parabasal, squamous, leukocytes) were identified and counted, ultrasound examination was done on 14th day of the cycle, that divide the sample into ovulatory and an ovulatory subgroups accordingly.Results: At the 2nd day of the cycle, there was a significant reduction in squamous cell count, highly significant increase in leukocyte, E2 hormone level increased markedly, with a significant negative correlation to leukocytes cells in patients' groups at P?0.05. Squamous cells of vaginal smear attained more acidophilic cytoplasm and increase in nuclear pyknosis. At the 14th day of the cycle, a significant increase in squamous cells count at P?0.05, cornified squamous cells predominantly seen associated with low ovulation rates of 44%. Ovulation showed significant reduction in parabasal cells count in patients group at P?0.05. At 21st day of the cycle, progesterone level was reduced with a significant reduction in squamous cells, parabasal cells and leukocytes counts in patients, with no significant correlation between progesterone and vaginal cytology cells, squamous cells consisted of mature cornified cells that seen predominantly in vaginal smear.Conclusion:Hormonal changes in PCOS presented mainly by the effect of elevated E2 hormone, that associated with increase in squamous cells count and cornification, with reduction in leukocytes and parabasal cells toward mid cycle. Progesterone hormone exert no significant effect on vaginal cytology in PCOS.Keywords: PCOS, vaginal cytology, ovulationCitation: Huda R. Kareem, Haider A. Jaafer, Zainab H. Hashim. The role of estrogen and progesterone on vaginal cytology during proliferative and secretary phases of menstrual cycle in women with polycystic ovarian syndrome. Iraqi JMS. 2017; Vol. 15(1): 78-87. doi: 10.22578/IJMS.15.1.10